A short history of microbial biofilms and biofilm infections. Issue 4 (April 2017) - Høiby, Niels
Abstract : The observation of aggregated microbes surrounded by a self‐produced matrix adhering to surfaces or located in tissues or secretions is old since both Leeuwenhoek and Pasteur have described the phenomenon. In environmental and technical microbiology, biofilms, 80–90 years ago, were already shown to be important for biofouling on submerged surfaces, for example, ships. The concept of biofilm infections and their importance in medicine was, however, initiated in the early 1970s by the observation of heaps of Pseudomonas aeruginosa cells in sputum and lung tissue from chronically infected cystic fibrosis patients. The term biofilm was introduced into medicine in 1985 by J. W. Costerton. During the following decades, the number of published biofilm articles and methods for studying biofilms increased rapidly and it was shown that adhering and nonadhering biofilm infections are widespread in medicine. The medical importance of biofilm infections is now generally accepted and guidelines for prophylaxis, diagnosis, and treatment have been published.